Encapsulation for efficient cryopreservation - Memon Kashan; Zhang Bing; Fareed Muhammad Azam; Zhao Gang (Frigid Zone Medicine)
Cryopreservation is a fundamental technology in biomedical research, regenerative medicine, and tissue engineering, enabling the long-term storage of cells, tissues, and organs. However, its effectiveness is limited by challenges such as intracellular ice formation, cryoprotectant toxicity, and reduced post-thaw viability. This review explores the crucial role of encapsulation in enhancing cryopreservation efficiency, with a focus on recent advances in materials science, bioengineering, and cryobiology. Emerging technologies, such as nanotechnology and stimuli-responsive polymers, are transforming encapsulation strategies. Innovations such as microfluidic systems offer precise control over cooling rates and cryoprotectant distribution, thereby mitigating conventional limitations. The review also addresses current obstacles related to scaling up encapsulation processes and ensuring the long-term biocompatibility and stability of preserved specimens. By synthesizing recent findings, this work provides a comprehensive resource for researchers and clinicians seeking to enhance biopreservation techniques and their applications in contemporary medicine and biotechnology. Finally, the review identifies critical knowledge gaps that must be addressed to improve the efficacy of cryopreservation strategies and advance their clinical translation.